A path toward disability-inclusive health in Zimbabwe Part 2: A qualitative study on the national response to COVID-19 - Tracey Smythe; Thubelihle Mabhena; Shepherd Murahwi; Tapiwanashe Kujinga; Hannah Kuper; Simbarashe Rusakaniko (African Journal of Disability, 2022)
Background: People with disabilities are at higher risk of adverse coronavirus disease 2019 (COVID-19) outcomes. Additionally, measures to mitigate COVID-19 transmission have impacted health service provision and access, which may particularly disadvantage people with disabilities.